Time-domain simulation of milling processes including process damping. (August 2020) - Denkena, B.; Grabowski, R.; Krödel, A.; Ellersiek, L.
Abstract: Process damping is an important effect in preventing chatter vibrations. However, common modelling approaches, e.g. semi-discretization and zero order solution, can not consider the non-linear behaviour of process damping. A further approach is the time-domain simulation, which simulates an entire cutting process in time-discrete steps. In this paper, a time-domain simulation is developed, which considers the process damping effect of flank face chanmfers. Process damping is considered by calculating the volume of the workpiece material which is indented by the flank face. Moreover, a stability criterion based on the force signal in frequency-domain is established. The simulation is used to create stability charts for unchamfered and chamfered tools. The calculated stability limits are compared with experimental data and stability limits calculated with the semi-discretization method. The results show a good agreement between calculated and experimental stability charts for an unchamfered tool. However, significant deviations exist between calculated and experimental stability charts for the chamfered tools. Possible causes, e.g. the neglection of plastic deformations and thermal loads, are discussed at the end of the paper.